2014
DOI: 10.1038/npp.2014.187
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genetic Factors Influence Amygdala Volumes and Risk for Alcoholism

Abstract: Alcohol abuse and dependence (alcohol use disorders, AUDs) are associated with brain shrinkage. Subcortical structures including the amygdala, hippocampus, ventral striatum, dorsal striatum, and thalamus subserve reward functioning and may be particularly vulnerable to alcohol-related damage. These structures may also show pre-existing deficits impacting the development and maintenance of AUD. It remains unclear whether there are common genetic features underlying both subcortical volumes and AUD. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 44 publications
5
43
2
Order By: Relevance
“…These results converge with previous findings of atypical morphology of the orbitofrontal cortex and amygdala among adolescent offspring from multiplex, alcohol-dependent families (Benegal et al, 2007; Dager et al, 2015; Hill et al, 2001; Hill et al, 2010; Hill et al, 2013; Hill et al, 2009b), as well as adults with AUD (Durazzo et al, 2011; Makris et al, 2008). Taken together, these results suggest that inherited abnormalities in amygdala and OFC may contribute to the high prevalence of SUDs in individuals with a family history of alcoholism (Cloninger et al, 1981; Hill et al, 2008; Hill et al, 2011; Verhulst et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results converge with previous findings of atypical morphology of the orbitofrontal cortex and amygdala among adolescent offspring from multiplex, alcohol-dependent families (Benegal et al, 2007; Dager et al, 2015; Hill et al, 2001; Hill et al, 2010; Hill et al, 2013; Hill et al, 2009b), as well as adults with AUD (Durazzo et al, 2011; Makris et al, 2008). Taken together, these results suggest that inherited abnormalities in amygdala and OFC may contribute to the high prevalence of SUDs in individuals with a family history of alcoholism (Cloninger et al, 1981; Hill et al, 2008; Hill et al, 2011; Verhulst et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Previous research indicates that compared to healthy controls from low-risk families, adolescent and young adult offspring with a family history of AUD show volumetric reductions in the right hemisphere of the orbitofrontal cortex (OFC) (Hill et al, 2010; Hill et al, 2009b) and the amygdala (Benegal et al, 2007; Dager et al, 2015; Hill et al, 2001; Hill et al, 2013). These results have been observed in samples where either the majority of cases had not yet developed a substance use disorder (Dager et al, 2015; Hill et al, 2001), were alcohol-naïve (Benegal et al, 2007), or the reduction in volume was seen even when cases with substance use disorder were removed (Hill et al, 2013; Hill et al, 2009b). Adults with AUD also show volumetric reductions of the OFC and amygdala compared to healthy controls (Durazzo et al, 2011; Makris et al, 2008), and atypical structure and function of these regions may be one biological mechanism that confers risk for SUDs.…”
Section: Introductionmentioning
confidence: 99%
“…Hill’s group has found that the offspring of alcoholic relatives had lower [right > left] asymmetry ratios of combined gray and white orbital volume, and that orbital white matter asymmetry in these offspring correlated with greater impulsivity (Hill et al, 2009). The same group (Hill et al, 2001, 2013) and Dager et al (2015) also detected loss of right amygdala volume in the adolescent offspring of families with alcoholism. Most recently, Cservenka et al (2015) reported that family history density was related to left nucleus accumbens volume in adolescents, although only in girls.…”
Section: Discussionmentioning
confidence: 67%
“…While there are inherent difficulties in resolving brain volumes as a function of premorbid condition or outcome of alcohol exposure, another confounding factor may be sex: binge drinking men showed smaller prefrontal, striatal, and medial temporal lobe volumes relative to non-binge drinking men, but binge drinking women showed the inverse pattern of larger volumes of these areas relative to non-binge drinking women (Kvamme et al, 2016). A recent study of 872 Mexican-American individuals evaluating subcortical volumes suggested that amygdala volume, but not volumes of hippocampus, caudate, putamen, pallidum, or thalamus, is sensitive to genetic predisposition for AUD (Dager et al, 2015). In an fMRI study, adolescents that were family history positive for AUD showed a pattern of nucleus accumbens connectivity to supplementary sensorimotor area and precuneus that correlated positively with and mediated the relationship with sensation seeking and also with total volume of alcohol consumed (Weiland et al, 2013).…”
Section: Introductionmentioning
confidence: 99%